Reorientasi Pendidikan Kristen Melalui Teologi Persahabatan - Yornan Masinambow (EDULEAD: Journal of Christian Education and Leadership, 2023)
This article aims to stressed friendship to embrace and then to empower Christian education so can be a friendly, egaliter, or emancipatory reorientation occurs between educators and learners through mutual interaction. The reorientation of Christian education through friendship theology is believed to be able to dismantle the reality of the authoritarian, superior, top-down Christian education praxis with a hierarchical face. Reorientation of Christian education through friendship theology believed can be able to dismantle the reality of the authoritarian, superior, top-down Christian education praxis with a hierarchical perspective. This article uses a descriptive qualitative approach where the author describes the theories about friendship theology and Christian education related to the purpose of writing this article, then brings them together through an interpretive study. The results of this study offer at least four aspects of friendship theologically for the reorientation of Christian education, namely; Christian education on shared story friendship where friendly relations between educators and students are emphasized to share everyday stories, Christian education on the friendship of love with respect and respect for one another, Christian education on the friendship of reciprocal commitments, where equal equality relations, doing hospitality, the common good. Then the Christian education of friendship to implement a shared vision where dialogue exists, and continues to build a balanced learning process as friends dynamically. AbstrakArtikel ini hendak menekankan teologi persahabatan yang merangkul, memberdayakan pendidikan Kristen agar terjadinya reorientasi ramah, egaliter atau emansipatoris antara pendidik dan peserta didik melalui interaksi bersama. Reorientasi pendidikan Kristen melalui teologi persahabatan diyakini mampu membongkar realitas praksis pendidikan Kristen yang otoriter, superior bersifat top-down yang berpandangan hierarkis. Artikel ini menggunakan pendekatan kualitatif deskriptif dimana penulis mendeskripsikan teori-teori seputar teologi persahabatan dan pendidikan Kristen yang terkait tujuan penulisan artikel ini, kemudian memercakapkan keduanya melalui pengkajian interpretatif terhadapnya. Hasil penelitian ini menawarkan setidaknya empat aspek persahabatan secara teologis untuk reorientasi pendidikan Kristen yakni; pendidikan Kristen persahabatan shared story dimana relasi sahabat antara pendidik dan peserta didik ditekankan untuk berbagi cerita sehari-hari, pendidikan Kristen persahabatan cinta kasih dengan adanya rasa hormat serta menghargai satu dengan yang lain, pendidikan Kristen  persahabatan komitmen timbal-balik, dimana relasi persamaan yang setara, melakukan keramahan, kebaikan bersama. Kemudian pendidikan kristen persahabatan untuk menerapkan visi bersama dimana hadirnya dialog, dan terus membangun proses pembelajaran yang seimbang sebagai sahabat secara dinamis.